The Role of Principal Leadership in Improving the Quality of Education - Oktapia, Dina; Nasution, Inom (Graduate Program Magister Manajemen Pendidikan, 2025)
This study aims to analyze the principal's leadership role in improving the quality of education at SMPN 4 Gunung Tuleh, a school located in a remote area with various limitations. This research approach uses ethnographic qualitative methods through in-depth interviews with the principal and several teachers. The results show that the principal's leadership plays an important role in building collaboration with various parties, such as the education office, school committee, teachers and the community. Quality improvement strategies are carried out through strengthening facilities and infrastructure, although limited, as well as learning innovations carried out by teachers. Teacher creativity in overcoming limitations, such as utilizing the surrounding environment as a learning medium and using active methods, is a supporting factor for successful learning. The conclusion from this study is that collaborative, humanist and adaptive leadership has a significant impact on improving the quality of education, even in conditions with limited resources. This study recommends the need for continuous support from various parties to strengthen the role of schools in providing quality education services